2015
DOI: 10.1177/2168479015586002
|View full text |Cite
|
Sign up to set email alerts
|

Improved Label and Liver Warning for Nonprescription Acetaminophen Products

Abstract: Findings support revision of acetaminophen ODFLs to improve liver damage warnings and to optimize labeling likely to be useful in prevention of and response to overdose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Acetaminophen is a safe OTC analgesic when used as directed, but can cause liver injury when label doses are exceeded. A label comprehension study of revised liver damage warning for acetaminophen found that labels more clearly stating organ damage along with more prominent information about the seriousness of overdose and how to take action led to more accurate behavioral intentions than with existing OTC labeling [52]. Moreover, a within-subjects study found that perceived risk of liver damage for acetaminophen was higher when labels contained revised warnings from the FDA (“organ-specific warning label”) [53].…”
Section: Tests Of Modifications To the Drug Facts Labelingmentioning
confidence: 99%
“…Acetaminophen is a safe OTC analgesic when used as directed, but can cause liver injury when label doses are exceeded. A label comprehension study of revised liver damage warning for acetaminophen found that labels more clearly stating organ damage along with more prominent information about the seriousness of overdose and how to take action led to more accurate behavioral intentions than with existing OTC labeling [52]. Moreover, a within-subjects study found that perceived risk of liver damage for acetaminophen was higher when labels contained revised warnings from the FDA (“organ-specific warning label”) [53].…”
Section: Tests Of Modifications To the Drug Facts Labelingmentioning
confidence: 99%
“…While some authors continue to suggest more changes to the labels (e.g. format, content, organization, font size) could improve communication of the associated risks (King et al, 2011(King et al, , 2015Soller, Ho, & Lightwood, 2015;Trivedi, Trivedi, & Hannan, 2014); others have established that understanding a risk does not determine whether users will actually comply with a warning (Frantz, Young, Rhoades, & Wisniewski, 2005;Eric F Shaver et al, 2006). In fact, Goya et al 2012evaluated the old and new labels of OTC acetaminophen, and although the new labels were found to be better in increasing perception of the risk of liver damage, they expressed concerns whether users of OTC acetaminophen would actually comply with the better-perceived warning message and instructions (Goyal, Rajan, & Essien, 2012).…”
Section: The Controversy: Perception Implies Compliance?mentioning
confidence: 99%
“…It's moreover prescribed for youthful children in lower measurements. It's unsafe to require more than the recommended dosage as you'll harm your liver, which may be irreversible and lethal (Soller, Ho, & Lightwood, 2015;Yoon, Babar, Choudhary, Kutner, & Pyrsopoulos, 2016). Paracetamol available under a variety of brands and, it is often combined with other medications such as cold medications.…”
Section: Introductionmentioning
confidence: 99%